Предмет: Алгебра,
автор: homicevix228
7x(x-4)-x(6-x)
5ab(4a плюс 3b)-10a2 (2b - 4)
iramazurk:
7 умножить на (х - 4) , или 7х
Ответы
Автор ответа:
1
Объяснение:
вроде так как то бы ???))
Приложения:
Автор ответа:
0
Ответ:
Объяснение:
7х (х -4) - х (6 - х) = (7х² - 28х) - (6х - х²) = 7х² - 28х - 6х + х² = 8х² - 22х
(20а²b + 15ab²) - (20a²b - 40a²) =
20a²b + 15ab² - 20a²b + 40a² = 15ab² + 40a²
Похожие вопросы
Предмет: Химия,
автор: dhd35667
Предмет: Математика,
автор: annaburova87
Предмет: Математика,
автор: zacrevskaia
Предмет: География,
автор: Over003
Предмет: Математика,
автор: дима242524